'Straighten Up and Fly Right': Radical right attempts to appeal to the British LGBTQ+ community. (May 2023) - Foster, Russell David; Kirke, Xander
This article explores an emerging strategy by sections of the British radical right towards the LGBTQ+ (lesbian, gay, bisexual, transgender and queer) community, who the radical right claim are existentially threatened by the alleged violent homophobia of Islam and their ostensible betrayal by 'the left'. Consequently, parts of the radical right present themselves as the 'true' protectors of LGBTQ+ individuals through what we term alter -progressivism. By analysing recorded speeches, discussions and interviews by and with key British radical right figures, we demonstrate three themes: (1) the broad radical right discourse of a 'Great Replacement' specifically tailored towards LGBTQ+ anxieties, (2) a narrative in which the radical right portray themselves as the defenders of (some) minorities and (3) an emerging distinction between the far-right and radical right concerning LGBTQ+ rights. We conclude that these themes represent a significant rhetorical shift and reveal the flexibility of radical right narratives in an attempt to appeal to diverse communities. This represents a serious challenge, which compels social scientists to adapt their understandings of radical right ideologies, objectives and strategies.